Effect of Addition of Alccofine on the Compressive Strength of Cement Mortar Cubes - Balamuralikrishnan R.; Saravanan J. (Ital Publication, 2021)
In the modern era, many research works are going on throughout the world for finding suitable cementitious material for the replacement of cement since it causes environmental pollution. In this order Fly ash, Silica fume, GGBS, Metakaolin, Micro materials, Quartz powder, etc. are tried out for replacing partially or fully the cement in concrete. A new ultrafine material called Alccofine (AF) which is manufactured from glass wastes is tried out for replacing partially in this research. Compressive strength is one of the important properties of cement. Strength tests are not made on neat cement paste because of difficulties of excessive shrinkage and subsequent cracking of neat cement. Cement mortar of 1:3 mix proportion is used to cast the cubes having an area of 50 cm2 are used for the determination of compressive strength of cement as per IS: 4031-1988 (Part-6). The graded Indian Standard sand (Ennore Sand -ES) confirming to IS: 650-1991 is used for preparing the cubes. In the same mix proportion, the same size cubes are cast with the River Sand (RS) to study the difference of the compressive strength between the Indian standard sand and river sand. Ordinary Portland cement (OPC) and Portland Pozzolana Cements (PPC) are used. The present study is the influence of Alccofine on cement mortar cubes by replacing the cement by Alccofine with various proportions like 5%, 10%, 15%, 20% were cast and tested in the laboratory as per Indian Standard 4301-1988 (Part-6) and the results were analysed and presented in the form of charts and graphs. It is observed that the early age strength is obtained for all the combinations but 10 percent of Alccofine yields more strength than other dosages. Doi: 10.28991/esj-2021-01265 Full Text: PDF